Improving reading comprehension learning for students with learning disabilities through know-want-learned strategy - Juhanaini, J.; Rizqita, Alya Jilan; Putri, Lamina Amalia (Jurnal Cakrawala Pendidikan, 2025)
Reading comprehension is a crucial skill that needs to be mastered. It helps individuals to understand the context and message through reading. For students with learning disabilities, mastering reading comprehension skills is particularly important. This research focuses on enhancing the reading comprehension of these students using the Know-Want-Learned (KWL) strategy. The study involved three experts who validated the instrument and included eight students with learning disabilities as participants. A mixed-methods approach was utilized, combining both quantitative and qualitative data to evaluate the effectiveness of the KWL strategy. Pre- and post-tests were conducted to measure improvements in reading comprehension levels, while interviews revealed the students' experiences and perceptions of the strategy. The results showed a significant increase in reading comprehension scores among the participants, highlighting the effectiveness of the KWL strategy in aiding understanding and information retention. Furthermore, qualitative feedback indicated that students felt more engaged and motivated during reading activities, as the KWL strategy prompted them to tap into their prior knowledge and establish learning goals. This research emphasizes the need for customized instructional strategies for students with learning disabilities, showcasing the KWL method as a valuable resource for enhancing reading comprehension. Future research should investigate the long-term impacts of this strategy and its relevance in various learning environments.